Integration of Maqashid Shariah Values and SDGs in Food Management: A Qur'an-Based Conceptual Study - Rofiq, Mokhammad Ainur; Khusnudin (Journal of Islamic Economics and Finance Studies, 2025)
Food security remains a critical challenge both globally and in Indonesian, marked by persistent hunger, unequal distribution, and environmental degradation. Maqashid shariah, the ultimate objective of Islamic law, provides a holistic framework through the preservation of life (hifz an-nafs), wealth (hifz al-mal), and the environment (hifz al-bi'ah). This study explores how the core of Qur'anic-based maqashid shariah values - halal-thayyib, equitable distribution, and sustainability - align with the Sustainable Development Goals (SDGs), specifically Zero Hunger (SDG 2) and reducing inequality (SDG 10). Employing a thematic interpretation (mawdu'i) approach, Qur'anic verses and commentaries from classical and Indonesian scholars the findings reveal that maqashid shariah underpin the foundation of an ethical food system by promoting instruments such as zakat, infaq, and sadaqah, which facilitate equitable access and ecological balance. The study proposes a conceptyal model integrating hifz an-nafs, hifz al-mal, and hifz al-bi'ah with the multidimensional aspect of food security, grounded in Qur'anic directives on food access, wealth redistribution, and environmental stewardship. This research offers a novel framework for sustainable food systems in Indonesia and presents practical implications for zakat-based food programs and sustainable agriculture policies, especially through stakeholders such as the National Zakat Agency (BAZNAS).